Optimal hemostasis duration for percutaneous coronary intervention via the snuffbox approach: A prospective, multi-center, observational study (HEMOBOX). (1st September 2021) - Roh, Ji Woong; Kim, Yongcheol; Takahata, Masahiro; Shiono, Yasutsugu; Kim, Hee-Yeol; Jeong, Myung Ho; Akasaka, Takashi
Abstract: Background: Percutaneous coronary intervention (PCI) via the distal radial access (DRA), called as snuffbox approach, recently has been increased worldwide due to fewer complications. Generally, since the diameter of distal radial artery is smaller than the radial artery, it is expected that the hemostasis duration can be shortened; however, there are no prospective studies. Furthermore, there is a lack of data about the feasibility of DRA for PCI. Methods: We prospectively collected data from 250 patients who were performed PCI via the DRA by three multi-center operators between March 2019 and December 2019. The primary outcome was hemostasis duration. Secondary outcomes were success rate of PCI, cannulation time, and puncture site complications. Results: Mean age of study population was 65.1 ± 10.3 years, success rate of PCI via the DRA was 99.2% (250/252) and 91.2% (228/250) patients was performed PCI via 6-French sheath. The cannulation time was 131 ± 98 s and the average hemostasis duration was 199 ± 50 min, and the median time was 180 [180–200] min. There are few minor hematomas (8.0%) and puncture site numbness (1.6%) with no radial artery occlusion. Conclusions: HEMOBOX trial first reported hemostasis duration for PCI using the DRA, approximately 3 h, with 99.2% success rate and few minor complications. Trial registration: https://clinicaltrials.gov/ct2/show/NCT03863652 Highlights: Successful hemostasis was achieved approximately 3 h after PCI via the DRA. This new approach showed a high success rate of PCI and an absence of major access-site complications. The DRA could be suitable for the alternative access-site for PCI in selected patients, such as those with a very high bleeding risk.